A new xanthene‐based two‐photon fluorescent probe for the imaging of 1, 4‐dithiothreitol (DTT) in living cells. (21st June 2018) - Wang, Chao; Dong, Baoli; Kong, Xiuqi; Zhang, Nan; Song, Wenhui; Lin, Weiying
Abstract: 1, 4‐Dithiothreitol (DTT) has wide applications in cell biology and biochemistry. Development of effective methods for monitoring DTT in biological systems is important for the safe handling and study of toxicity to humans. Herein, we describe a two‐photon fluorescence probe (Rh‐DTT) to detect DTT in living systems for the first time. Rh‐DTT showed high selectivity and sensitivity to DTT. Rh‐DTT can be successfully used for the two‐photon imaging of DTT in living cells, and also can detect DTT in living tissues and mice.